Social and Economic Mapping Sisi Madura dan Sisi Surabaya dalam Mendukung Tata Ruang Suramadu - Hakim, M. Andri (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2009)
The view of the Madura as the isolated area and low investment attractiveness, to be turned toward the post-development of Suramadu Bridge. Madura become potential and suitable investment area. Therefore, land use on the side of Surabaya and Madura must be controlled or defined as